Development of Filipino Inclusive Education Attitude Scale (FIEAS) - B. Formoso, Darlina (International Journal of Psychosocial Rehabilitation, 2019)
The Philippines follows the lead of other countries in embracing and practicing inclusive education. It recognizes that all children must be educated in the regular schools together with children their age. Teachers in the public schools are mandated by the law and by the Department of Education (DepEd) to practice inclusion in their classrooms. To be successful, researchers say that it is important for the teachers as implementers of the policy, to have a positive attitude towards inclusion, otherwise all efforts will be futile. This paper intended to adapt and develop an attitude scale that will measure how the Filipino teachers accept inclusion. It was based on the attitudes scale originally developed by Noto (2015) for teachers in the United States of America (USA). Four experts in the field of research and two in the field of Special Education examined the items for content validity. One hundred eighty one pre-service teachers participated in the first field testing. Scores on the field testing were subjected to internal consistency for reliability and factor analysis for construct validity. Results show that the instrument is valid and reliable measure of Filipino pre-service teachers’ attitudes toward inclusion. The study recommends to administer the attitude scale to in-service teachers in both the elementary and secondary schools. Comparative studies may be undertaken for further validation of the instrument.